COMPLAINT MANAGEMENT PADA SEKRETARIAT JENDERAL DEWAN PERWAKILAN RAKYAT REPUBLIK INDONESIA - Putera, Arifin Fajar; Hasniati, Hasniati; Tamma, Sukri; Amalia , Ayu (Jurnal Administrasi Negara, 2024)
Public trust in the performance of the bureaucracy in parliament is increasingly weakening because the apparatus is deemed not to show professionalism in completing its duties. This is reflected in the number of complaint letters that have not been resolved. Complaint handling strategies are an important part of managing community relations towards public participation. The Secretariat General of the House of Representatives of the Republic of Indonesia is required to provide quality services in accordance with established standards and be accessible to all levels of society. This research aims to analyze complaint services at the Secretariat General of the Indonesian People's Representative Council. The research method uses a qualitative descriptive approach. Data collection techniques in this research include interviews, observation and document review. This research uses four important aspects in handling complaints, which consist of empathy, responsiveness, fairness, and accessibility. Data collection was carried out in this research through direct interviews with informants who served at the Secretariat General of the House of Representatives of the Republic of Indonesia who were considered able to provide information related to complaint management. The results of research conducted at the Secretariat General of the People's Representative Council of the Republic of Indonesia regarding complaint management can be said to be quite good. However, there are still several aspects that need to be improved in complaint management, such as empathy, fairness and responsiveness